Psycho-oncological burden in patients with brain metastases undergoing neurological surgery - Araceli, Tommaso; Fischl, Anna; Haj, Amer; Doenitz, Christian; Stoerr, Eva-Maria; Hillberg, Andrea; Vogelhuber, Martin; Rosengarth, Katharina; Riemenschneider, Markus J.; Hau, Peter; Blazquez, Raquel; Pukrop, Tobias; et al. (Frontiers in Oncology, 2024)
PurposeThe development of brain metastases (BM) can significantly increase the psycho-oncological burden in cancer patients, requiring timely intervention. In addition, this aspect may negatively affect the course of the disease and treatment outcome. However, screening for psycho-oncological burden is often overlooked in clinical routine. Therefore, we analyzed the extent of psycho-oncological distress in a patient population with BM receiving neurosurgical resection and identified clinical characteristics associated with a high need for psycho-oncological intervention.MethodsWe prospectively screened 353 patients (169 female, 184 male, mean age 61.9 years) scheduled for microsurgical resection of one or more BM. Psycho-oncological screening was performed on the day of admission using the Hornheider screening instrument (HSI) and the distress thermometer (DT). Screening results were correlated with demographic and clinical data.ResultsMost patients (73.1%) completed the screening questionnaire. Patients who failed to complete the questionnaire presented more frequently with metachronous BM (74.7% vs. 25.3%, p=0.009), were significantly older (p=0.0018), and had a significantly lower KPS score (p=0.0002). Based on the threshold values of the questionnaires, 59.3% of the patients showed a significant psycho-oncological burden requiring immediate intervention. Univariate analysis demonstrated that synchronous BM (p=0.034), tumors in eloquent areas (p=0.001), lower KPS (p=0.031), female gender (p=0.009), and presurgical aphasia (p=0.042) were significantly associated with high psycho-oncological burden. Multivariate analysis showed synchronous BM (p=0.045), female gender (p=0.005), and lower KPS (p=0.028) as independent factors associated with high psycho-oncological burden.ConclusionThe majority of patients with BM have a high psycho-oncological burden. Female gender, synchronous BM, and lower KPS are independently associated with a need for psycho-oncological intervention.